Pengaruh Motivasi Kerja, Lingkungan Kerja Terhadap Kepuasan Kerja dan Kinerja Pegawai Pada Badan Lingkungan Hidup Kabupaten Karanganyar - Fathonah, Siti; Wibowo, Tri Hendro (-)
This study aims to determine the effect of: 1). motivation on job satisfication, 2). Work environment on job satisfication, 3). motivation on performance, 4). Work environment on performance, 5). Job satisfication on employee's performance the Environment Agency of Karanganyar District.The data used in this study is the primary data collected through questionnaires given to employees at the Environment Agency of Karanganyar District as many as 49 people. Analysis tools used is the instrument test, regression analysis with an intervening variable (Path Analysis), linearity test,t-test,F-test,R square test, correlation analysis.Instrument test result show all of valid and reliable. The analysis showed that: 1). Motivation has positive effect and significant on job satisfication, 2). Work Environment has positive effect and significant on job satisfication, 3). Motivation has positive effect and significant on performance, 4). Work environment has positive effect and significant on performance, 5). Job satisfication has positive effect and significant on employees performance the Environment Agency of Karanganyar District.As a result, test the coefficient of determination show that value of total R Square by 0.72 means the variable performance of employees at the Environment Agancy of Karanganyar District is described by the variable of motivation and work environment leadership with the job satisfication as an intervening variable by 72% and the remaining 28% is describe other variables outside the model study.The result of path analysis showed that: a). direct infuence of motivation on employee performance is greater than indirect influence of motivation on employess performance with the mediation of job satisfication, b). direct influence of work environment on employee performance is greater tha indirect influence of work environment on employee performance with mediation of job satisfication so as to improve the employee performance is selected direct route.Keywords : motivation on job satisfication, work environment, job satisfication,performance